A Systematic Review of the Effectiveness of Ginger, Cinnamon, Turmeric, Curcumin, and Curcuminoids for Dyslipidemia Associated With Diabetes. (7th June 2021) - Haley-Zitlin, Vivian; Alasvand, Sepideh; Bridges, William
Abstract: Objectives: This systematic review explores ginger, cinnamon, turmeric, curcumin, and curcuminoids efficiency in improving the serum lipid profile of individuals with type 2 diabetes (T2DM). Methods: Randomized controlled trials (RCTs), reported without restriction in language, that evaluated the effectiveness of ginger, cinnamon, turmeric, curcumin and curcuminoids on lipid profile parameters (total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglyceride (TG)) in individuals with T2DM were investigated through January 2021. PubMed, FSTA, Web of Science, CINAHEL, MEDLINE, and Cochrane Library databases were searched using relevant keywords. The following information was extracted: first author's name, publication year, geographical location of study, study design, sample size, age and gender of participants from intervention and controls groups, intervention duration, time of the intervention, dose of spices, and type of intervention or control. Results: One thousand-thirty relevant articles were identified after searching the electronic databases followed by a manual search. After removing all duplicate articles, screening the title and abstract, and scrutinizing the full text based on the inclusion criteria, 28 studies remained with a sample size of 1049 eligible patients in the control arm and 1035 patients in the intervention arm. Spice supplements were provided in capsule form: ginger, 8; curcumin, 3; turmeric, 3; cinnamon, 11; curcuminoids, 3. Trial duration was one to three months. Conclusions: In general, ginger, cinnamon, turmeric, curcumin, and curcuminoids were associated with an improved lipid profile in the presence of type 2 diabetes. Therefore, these spices may be a potential source for modern dyslipidemia treatments in individuals with type 2 diabetes. Funding Sources: N/A.